# If $y'(t)=f(t,y(t))$ find $y''$ and $y'''$. [closed]

If $f: \mathbb{R}\rightarrow \mathbb{R}: (t,y) \mapsto f(t,y)$ is a differentiable function and $y:\mathbb{R}\rightarrow \mathbb{R}$ satisfies the differential equation:

$y'(t)=f(t,y(t))$

Find $y''$ and $y'''$.

Has anyone an idea how to solve such problems?

## closed as off-topic by Namaste, zhoraster, Davide Giraudo, C. Falcon, LeucippusJan 27 '17 at 0:18

This question appears to be off-topic. The users who voted to close gave this specific reason:

• "This question is missing context or other details: Please improve the question by providing additional context, which ideally includes your thoughts on the problem and any attempts you have made to solve it. This information helps others identify where you have difficulties and helps them write answers appropriate to your experience level." – Namaste, zhoraster, Davide Giraudo, C. Falcon, Leucippus
If this question can be reworded to fit the rules in the help center, please edit the question.

You have to use the "chain rule".

I will change slightly the notation for the sake of clarity :

Suppose that $\forall t\in\mathbb{R},\,u'(t)=f(t,u(t))$ where $f:\mathbb{R}\to\mathbb{R},\,(x,y)\mapsto f(x,y)$

Then you get :

$$u''(t)=\frac{d}{dt}(t)\,\frac{\partial f}{\partial x}(t,u(t))+\frac{d}{dt}(u(t))\,\frac{\partial f}{\partial y}(t,u(t))$$

or, simply stated :

$$u''(t)=\frac{\partial f}{\partial x}(t,u(t))+u'(t)\,\frac{\partial f}{\partial y}(t,u(t))=\frac{\partial f}{\partial x}(t,u(t))+f(t,u(t))\,\frac{\partial f}{\partial y}(t,u(t))$$

And, after differentiating twice :

$$u'''(t)=\left[\frac{\partial^2f}{\partial x^2}(t,u(t))+u'(t)\frac{\partial^2f}{\partial x\partial y}(t,u(t))\right]+\frac{d}{dt}\left[f(t,u(t))\right]\frac{\partial f}{\partial y}(t,u(t))+f(t,u(t))\left[\frac{\partial^2f}{\partial x\partial y}(t,u(t))+u'(t)\frac{\partial^2f}{\partial y^2}(t,u(t))\right]$$

And finally :

$$u'''(t)=\frac{\partial^2f}{\partial x^2}(t,u(t))+f(t,u(t))\frac{\partial^2f}{\partial x\partial y}(t,u(t))+\left[\frac{\partial f}{\partial x}(t,u(t))+f(t,u(t))\,\frac{\partial f}{\partial y}(t,u(t))\right]\frac{\partial f}{\partial y}(t,u(t))+f(t,u(t))\left[\frac{\partial^2f}{\partial x\partial y}(t,u(t))+f(t,u(t)\frac{\partial^2f}{\partial y^2}(t,u(t))\right]$$

which can be reduced, in standard notation, to :

$$\boxed{u''(t)=f_x+ff_y}$$

and

$$\boxed{u'''(t)=f_{xx}+2ff_{xy}+f_xf_y+ff_y^2+f^2f_{xy}}$$

Hint. Using the chain rule, we get $$y''(t) = \partial_t \def\f#1{f\bigl(#1\bigr)}\f{t,y(t)} + \partial_y \f{t,y(t)}y'(t) = \partial_t\f{t,y(t)} + \partial_y \f{t,y(t)}\f{t,y(t)}.$$ To compute $y'''$ just differentiate again and replace $y'(t)$ by $\f{t,y(t)}$, as we did above.

• If you write $\partial_y \f{t,y(t)}\f{t,y(t)}$ it's difficult to know what is to be differentiated with respect to $y$. Instead, try $\f{t,y(t)}\partial_y \f{t,y(t)}$ or $\left(\partial_y \f{t,y(t)}\right)\f{t,y(t)}$ – Arthur Jan 22 '17 at 10:56

after the chain rule we get $$y''=f_t+f_y\cdot y'$$ with $$y'=f$$ we get for the second derivative $$y''=f_t+f_yf$$ further we get $$y'''=f_{tt}+f_{ty}y'+f_{yy}y'^2+f_{yt}y'+f_yy''$$ substituting $$y'=f$$ we get $$y'''=f_{tt}+f_{ty}f+f_{yy}f+f_{yy}f^2+f_{yt}f+f_y(f_t+f_yf)$$

• I would suggest substituting $y'$ with $f$. – Arthur Jan 22 '17 at 10:55
• Hi Thanks, can you please elaborate how you get the first expression from the chain (and product?) rule. Thx – Averroes2 Jan 22 '17 at 12:03
• we have $$y'=f(t,y)$$ and $$y=y(t)$$ thus we get $$y''=f_t+f_y\cdot y'$$ since we have $$y=y(t)$$ using the chain rule – Dr. Sonnhard Graubner Jan 22 '17 at 12:06